How Corporations Conceal Profits and How to Understand Your Corporation's Financial Report (Book). - Winter, Sidney G.; Miller, Herbert E. (The Accounting Review, 1944)
Abstract Reviews the book "How Corporations Conceal Profits and How to Understand Your Corporation's Financial Report."